The Relationship of Self-Directed Learning Readiness and Learning Motivation Towards Learning Achievement of First Year Medical Students - Triastuti, N Juni (Universitas Muhammadiyah Surakarta, 2016)
Understanding Self-directed learning readiness (SDLR) as internal factors as well as high motivation to learn can certainly be used as a predictor for the success of the learning process, in which it will result in satisfactory achievement of student learning. This study analyzed the relationship of SDLR towards the student’s achievement, the relationship of learning motivation towards the student’s achievement, the relationships of SDLR and learning motivation towards the achievement of students in the first year medical students. This study involved 52 respondents who received a questionnaire on self-learning readiness and motivation questionnaires. The data were analyzed by using Spearman test. There was asignificant correlation between self-directed learning readiness (SDLR) and learning achievement with the strength of the correlation was 0.874 (p: 0,000), between learning motivation and learning achievement with the strength of the correlation of 0. 848 (p: 0,000), between self-directed learning readiness (SDLR) and motivation to learn towards academic achievement with strength of the correlation for 0.870 (p: 0,000). Overall, there was a relationship between self-directed learning readiness and learning motivation towards learning achievement in the first year medical students.